Labour content of international trade in intermediates : the case of Portugal - Martínez-Galán, Enrique (2017)
This paper addresses the relation between international trade and employment in Portugal with regard to the labour content of trade in intermediates. It considers both the overall level of employment and labour disaggregated by skills (high-skill, medium-skill and low-skill). The assessment makes use of the newly developed internationally linked inputoutput (IO) database named World Input-Output Database (WIOD), complemented with the Socio-Economic Accounts (SEA) for skill-types of labour. The period analysed – 1995-2009 - is the longest possible taking into account the two databases used. The amount of labour required to produce imported intermediates (exported intermediates) is taken as a proxy to the job effect of downward (upward) embeddedness of the country into Global Value Chains (GVCs). We conclude that intermediates’ exports are basically intensive in low-skilled labour although presenting a tendency to skill-upgrading during the period analysed, while intermediates’ imports are proportionally much more intensive in skilled labour, predominantly of a medium skill level, an expected result in a country of an intermediate level of development. We also concluded that the estimated net labour content of jobs in trade in intermediates in the final year of the period analysed was globally negative in 51 thousand jobs. Main net losses were observed with Brazil, People’s Republic of China and India, while main net gains were observed with Spain and France.